KOMPETENSI PEDAGOGIK DALAM TAFSIR AL-MISBAH - Achyar Zein; Syamsu Nahar; Hendra Zulfran (JP : JURNAL PENDIDIKAN, 2021)
Abstract: The purpose of this research is to explain the verses-ayat Alquran related to pedagogic competence. In this case the authors do research and study in the Qur'anic verses related to the pedagogic competence in the interpretation of Al-Misbah that aims to create teachers who are competent, faithful, and Taqwa to Allah swt. This type of research includes library research with the approach of education and the science of interpretation. It is then analyzed by using the content analysis method. The data sources used are Tafsir Al-Misbah as a primary data source and other supporting books related to pedagogic competence as a secondary data source. The method used is the method of Tahlili. The results of this study show that: firstly, there are verses that have the pedagogic competence of the teacher in the interpretation of Al-Misbah, one of which is how Allah swt teaches the Prophet Adam about the names of objects. Secondly, it exposes verses of the Qur'an associated with pedagogic tension indicators in the interpretation of Al-Misbah to create alignment between general pedagogic competence and pedagogic competence in the interpretation of Al-Misbah.Keywords: competence, pedagogic, Tafsir, Al-Misbah